Public Health Nursing Strategies to Overcome Multidimensional Barriers in Colorectal Cancer Screening: A Health Belief Model Approach with Clinical Translation in Mainland China - Zou, Zhenyu (Asian Pacific Journal of Cancer Care, 2025)
Objective: To systematically analyze multidimensional barriers to colorectal cancer (CRC) screening among mainland Chinese residents using the Health Belief Model (HBM) and establish the role of nursing in screening promotion. Methods: A cross-sectional online survey was conducted via the WJX platform (www.wjx.cn (www.wjx.cn)) from March 12–15, 2025, targeting mainland Chinese residents aged ≥18 years (n = 422). The self-developed Multidimensional Barriers to Colorectal Cancer Screening Questionnaire (19 closed questions) operationalized five HBM dimensions: perceived susceptibility, severity, benefits, barriers, and cues to action. Reliability was confirmed through Cronbach’s α (all dimensions >0.6, except perceived barriers α=0.59, deemed acceptable for exploratory research). Validity testing showed 93% of items aligned with theoretical dimensions; item Q8 (time cost sensitivity) was retained despite lower factor loading due to significant predictive value for screening delays (p=0.03). Quantitative analysis included composite barrier scoring and radar chart visualization. Results: Key barriers were: • Perceived susceptibility barriers (58.21%): Underestimation of personal CRC risk. • Perceived severity barriers (42.38%): Weak vigilance toward disease consequences. • Perceived benefits barriers (62.50%): Low acceptance of screening technology. • Perceived barriers (45.00%): Time sensitivity (49.52% demanded ≤1 hour) and distrust in primary care. • Cues to action barriers (36.07%): Low conversion of awareness to action, linked to distrust in non-tertiary hospitals (83.10% exclusively trusted tertiary hospitals) and official health channels (44.76% trusted National Health Commission sources). Nursing demonstrated unique advantages: evidence-based education improved risk cognition, standardized nursing protocols reduced screening anxiety, and nurse-led models enhanced screening compliance. Conclusion: The study identifies perceived benefit and susceptibility barriers as primary obstacles to CRC screening in mainland China. Quantitative evidence supports nursing’s critical role in over-coming multidimensional barriers through risk communication, technical implementation, and outcome management. Findings indicate the necessity of integrating HBM constructs into nursing-led screening frameworks to optimize CRC screening accessibility.